Antibacterial Activity of Papaya Fruit (Carica papaya L) Ethanol Extract Against Escherichia coli - Jendri Korisano; Ivonne Mona Selly Panjaitan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The increasing occurrence of antibiotic resistance highlights the critical necessity to investigate other antibacterial options, especially those originating from natural materials. Papaya (Carica papaya L.) is a tropical species recognized for having multiple bioactive substances that may exhibit antibacterial properties. The study aimed to assess the antibacterial activity of papaya fruit pulp extract at concentration of 40%, 50% and 60% against Escherichia coli with four replications. The extract was prepared using an appropriate extraction technique and evaluated through an in vitro antibacterial assay. Antibacterial activity was determined by measuring the inhibition of bacterial growth in comparison with a control group. Findings revealed that papaya fruit pulp extract exhibited strong inhibitory effects against Escherichia coli. There was no significant difference between concentration (p value = 0.83). The result indicates that papaya fruit pulp may represent an alternative source of antibacterial compounds and support its further development for antimicrobial applications. This study expands the scientific understanding of papaya fruit pulp as a promising natural antibacterial resource.